THE MIGRATION SITUATION IN KAZAKHSTAN - BAIGAZIN, Meiram (CENTRAL ASIA AND THE CAUCASUS, 2004)
International migration of the population today is a multifaceted phenomenon which is having an impact on all aspects of social development. Regulation of this phenomenon is a specific area of government social policy carried out on the basis of administrative-legal, organizational-eco-nomic, informational, and other measures. During the course of integration development and universal globalization, migration of the population on a world scale is playing an important role in co-operation among the entities of international relations. Nevertheless, the existing control mechanisms are failing to deal with the growing migration flows. As a member of the world community and by virtue of its geographic location, our republic is actively participating in migration and in resolving the problems associated with it. For example, in February 2000, the government created an interdepartmental working group for drawing up and implementing migration policy. It defines the priority areas in cooperation with international organizations with regards to migration: registration of in-ternal immigration and departure of the population beyond the country, registration of foreigners, integration of ethnic Kazakhs, border control, the prevention of illegal migration and movement of people, their exploitation, and so on. What is more, this group has drawn up a conception and government action plan in this area for 2001-2010, defining in particular the priorities for resolving demo-graphic and migration problems and the mechanisms for carrying them out in the midterm (2001-2005) and long term (2005-2010). In the midterm, the following main tasks must be resolved: creating conditions to reduce emigration, improving the negative balance and integration in foreign migration, helping former compatriots to return home, rendering oralmans (repatriates) comprehensive assistance to settle down and adapt to their new place of residence, and improving the migration control system and legislation in this area.